Tuberculous meningitis is a major cause of mortality and morbidity in adults with central nervous system infections in Kota Kinabalu, Sabah, Malaysia: an observational study. Issue 1 (December 2016) - Lee, Heng; William, Timothy; Menon, Jayaram; Ralph, Anna; Ooi, Eng; Hou, Yan'an; Sessions, October; Yeo, Tsin
Abstract Background Central nervous system (CNS) infections are a significant contributor to morbidity and mortality globally. However, most published studies have been conducted in developed countries where the epidemiology and aetiology differ significantly from less developed areas. Additionally, there may be regional differences due to variation in the socio-economic levels, public health services and vaccination policies. Currently, no prospective studies have been conducted in Sabah, East Malaysia to define the epidemiology and aetiology of CNS infections. A better understanding of these is essential for the development of local guidelines for diagnosis and management. Methods We conducted a prospective observational cohort study in patients aged 12 years and older with suspected central nervous system infections at Queen Elizabeth Hospital, Kota Kinabalu, Sabah, Malaysia between February 2012 and March 2013. Cerebrospinal fluid was sent for microscopy, biochemistry, bacterial and mycobacterial cultures, Mycobacterium tuberculosis polymerase chain reaction (PCR), and multiplex and MassCode PCR for various viral and bacterial pathogens. Results A total of 84 patients with clinically suspected meningitis and encephalitis were enrolled. An aetiological agent was confirmed in 37/84 (44 %) of the patients. The most common diagnoses were tuberculous meningitis (TBM) (41/84, 48.8 %) and cryptococcal meningoencephalitis (14/84, 16.6 %).Mycobacterium tuberculosis was confirmed in 13/41 (31.7 %) clinically diagnosed TBM patients by cerebrospinal fluid PCR or culture. The acute case fatality rate during hospital admission was 16/84 (19 %) in all patients, 4/43 (9 %) in non-TBM, and 12/41 (29 %) in TBM patients respectively (p = 0.02). Conclusion TBM is the most common cause of CNS infection in patients aged 12 years or older in Kota Kinabalu, Sabah, Malaysia and is associated with high mortality and morbidity. Further studies are required to improve the management and outcome of TBM.